Differences in the labor market entry of second-generation immigrants and ethnic Danes - Nabanita Datta Gupta; Lene Kromann (IZA Journal of Migration, 2014)
Our study is one of the first to take search friction and cross-firm differences in factor productivity into account when investigating firm behavior towards second-generation immigrants in Denmark. We ensure sub-sample homogeneity in search models by matching second-generation immigrants to their ethnic Danish twins according to parental characteristics and informal network quality. We find that second-generation immigrants with a high-school or primary school education, in particular females, perform as well or better than their ethnic counterparts. Second generation immigrants with vocational education, in particular males, face lower arrival rates when unemployed and higher layoff rates than those of their twins.
Keywords: J15; J61; J71; 330; Firm behavior; Equilibrium search model; Matching; Second-generation immigrants